The Mesolithic hunter-gatherer camp site at Sammakko in Norrbotten, northernmost Sweden - archaeological finds and palaeoenvironmental reconstruction - Möller, Per; Palmbo, Frida; Nielsen, Anne Birgitte; Boman, Emma; Dong, Haoran; Björck, Svante; Cai, Yuanyang; Gimbe, Jannica; Macleod, Ruairidh; Shen, Mingjian; Wang, Yucheng; Westerlund, Mica; et al. (Geoarchaeology, 2024)
A small Mesolithic campsite near Sammakko in northernmost Sweden has been identified through its abundance of burnt bone and quartz refuse from stone tool manufacturing/ maintenance. Radiocarbon dating places hunter-gatherer activity here around 8900 years ago, 1800 years later than the oldest known settlement in Norrbotten, the Aareavaara site. Sediment stratigraphy in nearby lake basins suggests the final melting of stagnant ice, trapped in the undulating Veiki-moraine landscape, occurred around 9200 years ago. Initially after deglaciation, the area was covered with arctic heath, transitioning to an open birch forest by 9100 years ago. At the time of the Sammakko settlers, it was an open birch forest with elements of pine, and various dwarf shrubs, including dwarf birch, willow, and juniper. Common were also grasses, sedges and various herbs in the semi-open grounds. The settlers primarily relied on reindeer as indicated by burnt bones, with supplementary food sources such as pike and birds. Stalking was li